Abdominal internal oblique muscle injury in a tennis player - Maquirriain, J.; Ghisi, J. P. (Medicine and Science in Tennis, 2002)
Summary: Strain injuries of internal oblique abdominal muscles are uncommon in the athletic population. They often result from extreme, unbalanced, eccentric muscle contractions (in the adolescent injured athlete, avulsion iliac crest fracture should be ruled out). In sports involving heavy trunk rotational motions, such as tennis, special emphasis should be placed on hip and trunk strengthening.